Linking Different Sustainable Development Goals (SDGs) via Food Production Diversity: A Comparative Study of Two Countries in Arabian Desert - Liu, Suyu (European Journal of Sustainable Development, 2021)
There is a growing interest of the linkages between different SDGs as the interactions between SDGs are more and more observed. Food production diversity’s role in linking different SDGs deserves more attention, as it is directly related to a variety of SDGs such as SDG 1 (poverty reduction), SDG 2 (no hunger), and SDG 8 (economic growth and decent work). This article empirically examines the food production diversity in Saudi Arabia and Oman with Herfindal-Hirschmann Index, which measures food production diversity via the distribution of establishments and employees across 14 food production economic activities. It finds that in Saudi Arabia, the food production diversity is significantly lower and less changed than Oman. However, this may be caused by the much larger scale of food production in Saudi Arabia than Oman. Food production diversity is also possibly associated with cuisine culture, geographic location, and labor intensity in food production. However, there is insufficient evidence whether severe climate has an impact on food production diversity.